IMPLEMENTATION OF RESTORATIVE JUSTICE IN HANDLING THE CRIME OF CORRUPTION COVID-19 AID FUND - Putu Ari Sanjaya; Zulkarnein Koto; Marsudin Nainggolan (HERMENEUTIKA : Jurnal Ilmu Hukum, 2022)
The implementation of restorative justice (restorative justice) in the handling of corruption in the Covid-19 aid fund contained in Decision Number 8/Pid.Sus-Tpk/2021/PN.Jkt.Pst with the Defendant Harry Van Sidabukke, it can be seen that the panel of judges did not apply the concept of restorative justice. Because in its order, the Panel of Judges instead imposed a prison sentence of 4 (four) years on the Defendant. This means that the sanctions imposed by the judge still adopt the concept of retributive justice which focuses more on retaliation. The retaliation is manifested in the form of sentencing the Defendant. In addition, regarding the implementation of restorative justice in handling corruption cases of Covid-19 aid funds that need to be developed in Indonesian law enforcement, it is related to the provision of sanctions for the Defendant to focus more on recovering losses to state finances instead of focusing on retaliation. That is, in this case the application of the concept of restorative justice needs to be considered by the Panel of Judges so that the return of state losses becomes the main crime, not an additional crime. Because in the context of law enforcement in Indonesia, the restorative justice approach for corruption cases, both small-scale corruption and those that cause harm to state finances, has so far not been implemented. This is because the legal basis for the application of restorative justice for corruption cases in the internal prosecutor's office is not sufficient. This is because the current Attorney General's Regulation does not regulate corruption as a case that can be resolved through restorative justice.